Effects of maximum and minimum offers on reciprocity and trust perceptions during economic decision-making - Doheny, Margaret M.; Roque, Nelson A.; Lighthall, Nichole R. (Frontiers in Cognition, 2025)
IntroductionAlthough it is understood that previous betrayals affect future trust decisions, the degree to which this is true remains unclear in terms of frequency and severity. Additionally, it is currently unknown whether this relationship between the frequency and magnitude of received actions and subsequent trust decisions is mirrored when individuals experience acts of generosity. Prospect theory proposes that losses are weighed more heavily than gains, but the comparison between frequent, minor losses or gains and infrequent major losses or gains has yet to be explored.MethodsThe current study (n = 123) utilizes an adapted version of an economic trust game to examine the effects of minimum and maximum offerings on both reciprocations and perceptions of trust. Participants played the game with two partners: one who offered a maximum or minimum offer (extreme) and one who did not (stable), in either a high or low offer condition where all offers from the stable partner were above or below the median amount, respectively.ResultsThe results align with prospect theory in that minimum offers had a greater impact on both behavior and perceptions than equivalent gains (maximum offers).DiscussionThis study highlights complexities between trust, reciprocity, and perceptions of fairness, with implications for understanding social behavior in real-world settings.